1981
DOI: 10.1002/dev.420140314
|View full text |Cite
|
Sign up to set email alerts
|

Development of infant independence in a captive group of lowland gorillas

Abstract: In March 1976, 3 lowlands gorillas (Gorilla gorilla gorilla) were born to primiparous females living with an adult male in a large compound at the field station of the Yerkes Regional Primate Research Center of Emory University. Observations of parent and infant behavior began at the birth of the infants, using several methods of data collection. This report focuses on the development of independence in these infants over the 1st 1 1/2 years of life. As expected, measures of mother-infant contact and proximity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
3

Year Published

1982
1982
1999
1999

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 22 publications
4
22
3
Order By: Relevance
“…It seems likely that the increased mother-infant spatial proximity in the first week postretum was related to male aggressiveness. This would be consistent with our previous finding of maternal protectiveness in the early life of these infants being almost exclusively related to adult male inquisitiveness and aggressive dis plays [Hoff et al, 1981b]. Nadler [1980] has integrated the positions of Stewart [1977] and Weisbard and Goy [1976], and suggested that protection in the face of inquisi tiveness operates initially to establish close mother-infant contact, while social reinforcement serves to maintain such behavior through infancy.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It seems likely that the increased mother-infant spatial proximity in the first week postretum was related to male aggressiveness. This would be consistent with our previous finding of maternal protectiveness in the early life of these infants being almost exclusively related to adult male inquisitiveness and aggressive dis plays [Hoff et al, 1981b]. Nadler [1980] has integrated the positions of Stewart [1977] and Weisbard and Goy [1976], and suggested that protection in the face of inquisi tiveness operates initially to establish close mother-infant contact, while social reinforcement serves to maintain such behavior through infancy.…”
Section: Discussionsupporting
confidence: 80%
“…Our previous developmental reports of infant independence [Hoff et al" 1981b] and infant play [Hoff et al, 1981a] revealed a consistent malefemale infant difference in a number of mother-infant contact behaviors and in active social play. In the present study, we also found such differ ences within these behaviors across conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several laboratory studies have shown that among monkey motherinfant pairs housed in isolation infants ini tially spend less time in contact with their mothers and are rejected more than infants reared in social groups [Hinde and SpencerBooth, 1967;Wolfheim et al, 1970;Kaplan, 1972;Castcll and Wilson, 1971], These re sults have been explained by suggesting that the presence of group companions creates a more 'complex social environment ' [e.g.. Rosenblum, 1974a, b]. Similar data on chim panzee (Pan troglodytes) [Nicolson, 1977] and gorilla (Gorilla gorilla) [Hoff et al, 1980] development have been interpreted in a like manner.…”
Section: Introductionsupporting
confidence: 51%
“…At the age of 14 months, Moja's physical and motor development was visibly retarded in comparison with other mother-raised in fants of the same age [13,14], This was per haps caused by a (later identified) cardiac defect and/or by unrest in the group. Moja rarely moved away from his mother and gen erally tried to maintain physical contact with her.…”
Section: Maternal Carementioning
confidence: 99%
“…Modes of maternal transport [13] V entrolateral infant with ventrum in contact with the mother's side Grooming [ 1 ] Social examination [ 14] Sucking/nipple contact [ 14] Protect [14] Grab grasp an animal briefly with one hand Pull one individual pulls another animal's arm or leg towards itself Retrieve [14] …”
Section: 0 Weeksmentioning
confidence: 99%